Cover Image. Issue 3 (4th May 2022) - Hamer, Sarah A.; Ghai, Ria R.; Zecca, Italo B.; Auckland, Lisa D.; Roundy, Christopher M.; Davila, Edward; Busselman, Rachel E.; Tang, Wendy; Pauvolid‐Corrêa, Alex; Killian, Mary Lea; Jenkins‐Moore, Melinda; Torchetti, Mia Kim; et al.
Abstract : The cover image is based on the Short Communication SARS‐CoV‐2 B.1.1.7 variant of concern detected in a pet dog and cat after exposure to a person with COVID‐19, USA by Sarah A. Hamer et al., https://doi.org/10.1111/tbed.14122 .